Baeotingis Drake & Poor, 1939 and Coleopterodes Philippi, 1864 (Hemiptera: Heteroptera: Tingidae): first genera records for Brazil from Pampa - Guidoti, Marcus; Goldas, Camila Da Silva; Podgaiski, Luciana Regina; Mendonça, Jr., Milton De S. (Zootaxa, 2014)
Individuals of two genera, Baeotingis Drake & Poor, 1939, and Coleopterodes Philippi, 1814, were collected from natural grassland areas in Eldorado do Sul and Lavras do Sul municipalities, in Rio Grande do Sul state. This constitutes the first records of these taxa for Brazil. The distribution of these genera including all species was reviewed and a map with these geographical data is provided. We have discussed both geographical distribution patterns in the light of Morrone's biogeographical areas.